Sherman Alexie’s Literary Works as Native American Social Realistic Projections - Hossain, Md. Amir; Sarker, S.M. Abu Nayem (European Scientific Journal, ESJ, 2016)
This paper aims to look at the social realistic issues in the context of Sherman Alexie’s literary works. Alexie is one of the postmodern authors in the United States of America. He is very popular among his Native American society as well as community for representing social reality of his age. This paper is divided into several sections; each section shows a benchmark of the 21st century Social Picture of the Native Americans in the light of Alexian Literary Works. It also scrutinizes stories, and novels with a view to highlighting a faithful picture of Native Americans in the light of everyday social issues, including poverty, alcoholism, unhealthiness, racism, and suicidal act. Basically, the main part of my paper deals with social problems of Native Americans in the United States of America as depicted in Alexie’s literary works. It highlights an awareness of the Native Americans so as to keep themselves aloof from drug addiction, poverty, depression, and psychological trauma. Here I have also applied the critical theory of Social Realism with a view to unveiling a subtle literary affinity with Alexie’s works. In this study, I would like to show the significance of this study, and research methodology as well.